2021
DOI: 10.29089/2021.21.00190
|View full text |Cite
|
Sign up to set email alerts
|

Influence of heliogeophysical factors on patients with myocardial infarction

Abstract: Introduction: Global climate change is already affecting the health, living conditions, and livelihoods of people on all continents. According to many researchers, the deterioration of the patient's condition is manifested after a solar flare, with the onset of a magnetic storm. Aim: The aim of the article is to study the influence of heliogeophysical factors on the development and outcomes of myocardial infarction. Material and methods: Using data on the effect of space weather on a person from France, Germ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(21 reference statements)
0
0
0
Order By: Relevance
“…It has been demonstrated that geomagnetic storms may have a potential correlation with increased incidence of cardiovascular diseases, including myocardial ischemia and cerebral stroke. The intensity of radiation emitted on the Earth's surface is higher during wintertime due to the planet's proximity to the sun, which contrasts with the equatorial region where there is a higher incidence of cardiovascular diseases throughout the year due to increased radiation exposure [21].…”
Section: General Aspectsmentioning
confidence: 99%
“…It has been demonstrated that geomagnetic storms may have a potential correlation with increased incidence of cardiovascular diseases, including myocardial ischemia and cerebral stroke. The intensity of radiation emitted on the Earth's surface is higher during wintertime due to the planet's proximity to the sun, which contrasts with the equatorial region where there is a higher incidence of cardiovascular diseases throughout the year due to increased radiation exposure [21].…”
Section: General Aspectsmentioning
confidence: 99%